Perfis sociodemográficos da população sénior de Vila Nova de Gaia: de privilegiados a remediados e excluídos - Alves, Hélder; Machado, Idalina; Almeida, Sidalina; Guedes, Joana; Zilhão, Adriano; Ribeiro, Óscar (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2018)
Based on the diagnosis of the senior population of Vila Nova de Gaia, which is part of the elaboration of the Gerontological Plan of this county, this paper addresses the diversity of profiles of the seniors surveyed and demonstrates that old age is far from being homogeneous. Acknowledging this heterogeneity is fundamental for those assuming political and social intervention responsibilities since it promotes the development of social responses that must be appropriate to this diversity. In order to contribute to the adequacy of the responses to the considered population, and using statistical analysis procedures such as multiple correspondence analysis and clusters, this study identifies three main profiles: old age with privileged resources; old age making ends meet; old age with exclusion and withdrawal.